The brain and behavior an introduction to behavioral neuroanatomy - Clark, David L. 1939- (Cambridge University Press, 2005)
This new edition of The Brain and Behavior builds on the success of the previous edition and retains the core aim of providing an accessible introduction to behavioral neuroanatomy. Human behaviour directly reflects the anatomy of the central nervous system, and it is the goal of the behavioural neuroscientist to uncover the neuroanatomical basis of behaviour. Recent developments in neuroimaging technologies have led to significant advances on this front. The text is presented in a highly structured and organised format to help the reader distinguish between issues of anatomical, behavioural and physiological relevance. Simplified and clear diagrams are provided throughout the chapters to illustrate key points. Case examples are explored to set the neuroanatomy in the context of clinical experience. The book is written for behavioural clinicians, trainees, residents and students, and will also be of interest to psychiatrists, neurologists and neuroscientists seeking an accessible overview of behavioural neuroanatomy